Local and Remote Influences on the Heat Content of the Labrador Sea: An Adjoint Sensitivity Study. Issue 4 (19th April 2018) - Jones, Daniel C.; Forget, Gael; Sinha, Bablu; Josey, Simon A.; Boland, Emma J. D.; Meijers, Andrew J. S.; Shuckburgh, Emily
Abstract: The Labrador Sea is one of the few regions on the planet where the interior ocean can exchange heat directly with the atmosphere via strong, localized, wintertime convection, with possible implications for the state of North Atlantic climate and global surface warming. Using an observationally constrained ocean adjoint model, we find that annual‐mean Labrador Sea heat content is sensitive to temperature/salinity changes (1) along potential source water pathways (e.g., the subpolar gyre, the North Atlantic Current, the Gulf Stream) and (2) along the West African and European shelves, which are not significant source water regions for the Labrador Sea. The West African coastal/shelf adjustment mechanism, which may be excited by changes in along‐shelf wind stress, involves pressure anomalies that propagate along a coastal waveguide toward Greenland, changing the across‐shelf pressure gradient in the North Atlantic and altering heat convergence in the Labrador Sea. We also find that nonlocal (in space and time) heat fluxes (e.g., in the Irminger Sea, the seas south of Iceland) can have a strong impact on Labrador Sea heat content. Understanding and predicting the state of the Labrador Sea and its potential impacts on North Atlantic climate and global surface warming will require monitoring of oceanic and atmospheric properties at remote sites in the Irminger Sea, the subpolar gyre, and along the West African and European shelf/coast system, among others. Plain Language Summary: There are only a handful of locations on Earth where natural processes can rapidly inject heat and carbon into the interior ocean, where it can remain for decades to centuries, potentially slowing global surface warming. One of these locations is the Labrador Sea, which features strong exchanges of heat with the atmosphere and exceptionally deep mixing between the surface ocean and interior ocean. In this paper, we examine the factors that influence the heat content of the Labrador Sea. Using a numerical model, we find that although the heat content is most sensitive to local exchanges with the atmosphere, there is an unexpected connection between the heat content of the Labrador Sea and wind strength along the coast of West Africa and Europe. Sustained changes in wind strength in those regions can change the large‐scale circulation of the entire North Atlantic, ultimately changing the amount of heat that gets transported into the Labrador Sea and potentially impacting North Atlantic climate and global surface warming. Key Points: We use adjoint sensitivity fields to quantify possible influences on Labrador Sea heat content We identify a basin‐scale adjustment mechanism involving the West African and European shelves Nonlocal heat fluxes can have a considerable impact on Labrador Sea heat content